M.Psi Efektivitas Program Pelatihan Efikasi Diri Berbasis Rencana Tindakan Terhadap Peningkatan Grit Tenaga Penjualan dalam Bisnis Penjualan Berjenjang - Fauziah, Diani; Riasnugrahani, Missiliana; Kuntari, Indah Soca Retno (Universitas Paramadina, 2025)
This study aims to examine the effectiveness of an action plan-based self-efficacy training program in enhancing grit among salesperson in multilevel marketing business. Grit which encompasses perseverance of effort, consistency of interest, and adaptability to situations is viewed as a critical trait for confronting challenges in direct sales. The research design is a quasi-experiment employing a mixed-methods approach. The study involved 14 salespeople divided into experimental and control groups. The relatively small number of participants (n=14) is a limitation of this study, thereby restricting the generalizability of its findings. The training was conducted based on the sources of self-efficacy theory and implemented through experiential learning methods. It was followed by a two-week action planning session. Pretest and posttest assessments utilized the Employee Grit Scale (E-Grit) and the General Self-Efficacy Scale (GSES). Statistical analysis using the Wilcoxon SignedRank Test yielded a Z-score of -0.430 with an Asymp. Sig. (2-tailed) of 0.667 (p > 0.05). Although descriptive data suggested that most participants in the experimental group showed an increase in grit scores, the statistical test revealed no significant difference. This indicates that the training program did not conclusively improve grit from a statistical standpoint. However, behavioral change evaluations conducted six months post-intervention demonstrated enhanced work performance among participants, marked by increased self-confidence, resilience in facing rejection, and improved time management skills. These findings suggest the potential long-term effectiveness of the intervention.